New hominin dental remains from the ∼2.04-1.95 Ma Drimolen Main Quarry, South Africa - A. B. Leece; J. M. Martin; S. Baker; C. Wilson; D. S. Strait; G. T. Schwartz; A. I. R. Herries (Taylor & Francis Group, 2023)
Background The Drimolen Palaeocave site is situated within the UNESCO Fossil Hominid Sites of South Africa World Heritage Area and has yielded numerous hominin fossils since its discovery in 1992. Most of these fossils are represented by isolated dental elements, which have been attributed to either of two distinct hominin genera, Paranthropus and Homo. Aim This paper provides morphological descriptions for a further 19 specimens that have been recovered from the ∼2.04-1.95 Ma Drimolen Main Quarry (DMQ) deposits since 2008. This paper also discusses the two primary hypotheses used to explain Paranthropus robustus variation: sexual dimorphism, and micro-evolution within a lineage. Subjects and methods These 19 fossils are represented by 47 dental elements and expand the sample of DMQ early Homo from 13 to 15, and the sample of Paranthropus robustus from 69 to 84. Results The evidence presented in this paper was found to be inconsistent with the sexual dimorphism hypothesis. Conclusion Some support was found for the micro-evolution hypothesis.